BIOMASS ケイカク ニ オケル ニホン ノ カツドウ - 星合, 孝男; ホシアイ, タカオ; 村野, 正昭; ムラノ, マサアキ; 奈須, 敬二; ナス, ケイジ; 寺崎, 誠; テラザキ, マコト; Hoshiai, Takao; Murano, Masaaki; Nasu, Keiji; Terazaki, Makoto (1991)
P(論文) 南極海洋生物資源管理の基礎として, 南極海の海洋生態系の構造と動的機能をより深く理解することを目的としたBIOMASS計画は, 1977年から10ヵ年計画として実施された国際共同研究であった。1991年9月, ドイツ国, ブレーマーハーフェンで開催された研究成果総括のための"BIOMASS Colloquium"をもって, すべての活動を終結した。かねて南極海の生物資源, とくにナンキョクオキアミの利用の可能性について関心を持っていたわが国の研究者, 研究機関はBIOMASS計画に積極的に参加した。BIOMASS計画では, 1980-81年に第1回国際共同多船観測(FIBEX)計画を組み, ナンキョクオキアミ現存量のいっせい調査を行った。わが国からは, 海鷹丸, 白鳳丸, 開洋丸が参加した。また, 第2回国際共同多船観測(SIBEX)が, 1983-84,1984-85年の2期に分けて行われ, 第1期には海鷹丸, 開洋丸が, 第2期には開洋丸が航海を行った。第2回多船観測では, 調査・研究の力点は, 生態系全般の研究に移行した。国際多船観測とは別に, 海鷹丸, 開洋丸はそれぞれ独自の調査航海を行っているが, いずれも南極海の海洋生態系の解明を目的としたものであり, BIOMASSの一環と見ることができる。日本南極地域観測隊は, BIOMASS計画に合わせて, 船上における定常観測を拡充すると共に, 定着氷縁, 昭和基地周辺の定着氷域での研究を行った。これらの研究は, 観測・研究船の夏期開水域での研究成果と共に, 海氷域における冬期を含めた生態系の構造と機能についての基本的情報を提供した。これらの研究を通して, わが国の南極海海洋生態系に対する理解は格段に深まったと考えられる。これまでに発表された論文, 報告の数は, 200編を超える。 Japanese scientists have been interested in the utilization of Antarctic krill as a potential resource of protein for mankind. Thus, the objectives of BIOMASS which aimed at gaining the knowledge of Antarctic marine ecosystems for the management of Antarctic marine living resources were accepted by Japanese scientists and supported by the Japanese government. In succession to the pre-BIOMASS activities, Japanese vessels, UMITAKA MARU III, KAIYO MARU and HAKUHO MARU conducted cruises to participate in FIBEX and SIBEX. Furthermore, two additional cruises were undertaken by the KAIYO MARU as an extension of BIOMASS. The Japanese Antarctic Research Expedition contributed to BIOMASS with the observations onboard the FUJI and SHIRASE and shorebased research at Syowa Station. The UMITAKA MARU III and the HAKUHO MARU investigated primary production, abundance and distribution of phytoplankton, zooplankton and micronekton and organic particles with oceanographic conditions in the Southern Ocean south of Australia. The KAIYO MARU surveyed physical, chemical and biological conditions along several meridional lines and in grids in the Indian and Atlantic sectors of the Southern Ocean. Stress was put on the acoustic survey of the krill abundance and ...